2022
DOI: 10.1002/marc.202200372
|View full text |Cite
|
Sign up to set email alerts
|

Serpentine‐Inspired Strain Sensor with Predictable Cracks for Remote Bio‐Mechanical Signal Monitoring

Abstract: Flexible strain sensors have attracted intense interest due to their application as intelligent wearable electronic devices. However, it is still a huge challenge to achieve a flexible sensor with simultaneous high sensitivity, excellent durability, and a wide sensing region. In this work, a crack-based strain sensor with a paired-serpentine conductive network is fabricated onto flexible film by screen printing. The innovative conductive network exhibits a controlled crack morphology during stretching, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Soft wearable sensing devices have attracted extensive research attention in the fields of e-skin, human health monitoring, and medical image-assisted diagnosis due to the advantages of integrated functions, high sensitivity response, and good biocompatibility. However, the existing sensors are unable to achieve a highly sensitive response over a wide sensing range. , In addition, the sensors require external power supply during utilization. These conditions hinder the further development of flexible wearable sensing devices. Soft wearable sensing devices having both highly sensitive response over a wide sensing range and self-powered sensing characteristics are the key issues requiring a solution at present.…”
Section: Introductionmentioning
confidence: 99%
“…For example, flexible strain sensors based on MWCNTs/PDMS microspheres (MSs) showed a high strain range of more than 40% and high sensitivity (gauge factor, GF = 7.22); Ecoflex-based resistive-type sensors reinforced with CNTs showed a GF of 1–18 and a range of more than 200% with a linear response. Although they have a wide response range, the sensitivity is low. Then, the structure design of the sensor has been extensively studied to improve the sensitivity, such as the snake-like conductive network, lotus leaf micro-pattern, scorpion bionic, and interlocking structure. , For example, graphene oxide/PDMS composite membranes with the nano-crack structure on the surface have a very high sensitivity under 0–1% tension (maximum GF is 8699). These crack-based sensors have high sensitivity due to crack breaking and closing under strain or vibration.…”
Section: Introductionmentioning
confidence: 99%
“…24−26 Although they have a wide response range, the sensitivity is low. Then, the structure design of the sensor has been extensively studied to improve the sensitivity, such as the snake-like conductive network, 27 lotus leaf micro-pattern, 28 scorpion bionic, 29 and interlocking structure. 30,31 For example, graphene oxide/PDMS composite membranes with the nanocrack structure on the surface 20 have a very high sensitivity under 0−1% tension (maximum GF is 8699).…”
Section: Introductionmentioning
confidence: 99%